The system of secondary reference standards in drug quality control laboratories - D. A. Leontiev (Регуляторные исследования и экспертиза лекарственных средств, 2018)
Pharmaceutical reference standards systems have been analyzed. The imperfections of a one-level system have been demonstrated. It has been shown that for making a reliable decision on the quality of medicines one needs to use a two-level system, an important part of which is the system of secondary reference standards (SRS) of a facility. The article describes the experience in the development and implementation of the SRS system in Ukraine within the transition to a two-level system.